Planning, Public Policies and 2030 Agenda. The Case of Costa Rica - Arenilla Sáez, Manuel (Revista del CLAD Reforma y Democracia, 2023)
This article is the result of research based on the agreement signed in 2022 between the Ministry of National Planning and Economic Policy (MIDEPLAN) of Costa Rica and the Latin American Center for Development Administration (CLAD). Its purpose was to develop the “Design and management of public policies in the framework of the SDGs”. The institutional approach was applied and it was considered that good performance in meeting the SDGs would not be achieved if there is no strong institutional architecture to ensure governance and institutional capacity. The research considers two premises. On one hand, the need to strengthen institutions to ensure the viability of planning and improve SDG performance through public policies. On the other hand, the importance of adopting the challenges faced by the country, as well as its financial capacity, as criteria for planning and prioritization of institutions. It also draws from the case of Costa Rica a series of proposals that may be useful for the region. The conclusions and proposals include: 1) the need to create a transversal axis of governance based on the guidelines and indicators of international and supranational bodies; 2) the methodology and meaning of public policies must be specified; 3) the obligation to orient public policy indicators to the achievement of the common good; 4) the necessary linkage of public policies with the budget; 5) the need to implement a mechanism for monitoring policy compliance that includes common elements for all policies; 6) that the achievement of the SDGs is favored by aligning them with national and, where appropriate, international strategic plans, such as the 2030 Agenda; and 7) that the SDGs would be accelerated by the introduction of innovation and digitalization processes. The territorial aspect should also be taken into account and multilevel planning should be established.
Keywords: Planning; Sustainable Development; Public Policy; Institutional Development; Latin America; Costa Rica